Musik Kompang dalam Penciptaan Komposisi Musik “Kompangku” - Hamzaini Hamzaini; Yesriva Nursyam; Aan Nursyam; Ricky Warman Putra; Jhori Andela (FBS Universitas Negeri Padang, 2022)
The musical of composition